New Hg (II) Complex: As a Novel, Green and Efficient Reusable Catalyst for Synthesis of Polyhydroquinolines via Hantzsch Condensation - Ghasemi, Hengameh Deldar; Allameh, Sadegh; Beyramabadi, Safar Ali; Behmadi, Hossein; Morsali, Ali Morsali (Asian Journal of Biological and Life Sciences, 2018)
A novel Hg (II) complex based on 5-nitro-N1-((pyridin-2-yl) methylene) benzene-1,2-diamine (HgL2) has been studied for catalytic performance in the synthesis of polyhydroquinoline derivatives. This efficient and eco-friendly catalyst has been utilized in a one-pot four-component Hantzsch condensation of dimedone, aromatic aldehydes, ethyl acetoacetate and ammonium acetate under solvent and free-solvent conditions. Mild reaction conditions, simple work-up procedure, being environmentally friendly and high product yields are advantageous feature of this method
Keywords: Aromatic aldehyde; Hantzschcondensation; Hg(II) complex; Polyhydroquinoline